Flipped Classroom dalam Pembelajaran Biologi dan IPA: Implementasi dan Tantangan di Era Pembelajaran Abad 21 - Julham Hukom (CV. SINAR HOWUHOWU, 2026)
Biology and science education (IPA) presents distinctive pedagogical challenges due to its dual nature as a body of knowledge and a set of scientific processes. The Flipped Classroom (FC) model, which relocates direct instruction outside the classroom and dedicates face-to-face time to active, higher-order learning, has emerged as a promising pedagogical strategy for addressing these challenges. This article presents a systematic literature review of 15 primary studies published between 2018 and 2025 examining the implementation, effectiveness, and challenges of the Flipped Classroom model in biology and IPA education in Indonesia and globally. The review reveals that FC is implemented primarily in three forms in biology learning: traditional video-based flipping, FC integrated with active learning models (Discovery Learning, Problem-Based Learning), and FC supported by digital learning management systems. Evidence consistently demonstrates that FC significantly improves student learning outcomes, critical thinking skills, and learning independence. Key challenges identified include students limited digital access, insufficient teacher competence in producing quality digital learning content, and difficulties in ensuring student accountability for pre-class learning activities. This article concludes that FC is highly appropriate for biology and IPA education and offers recommendations for effective implementation, particularly in the context of the Merdeka Curriculum.